The Triumph of the Veiled Dance The Influence of Oscar Wilde and Aubrey Beardsley on Serge Diaghilev's Creation of the Ballets Russes - Rutherford, Annabel (Edinburgh: Edinburgh University Press, 2009)
RESUMEN: The tremendous impact that Serge Diaghilev's Ballets Russes made on twentieth-century western arts has been well documented by scholars. Rarely has a theatre art made such an impact on society. And this influence spread beyond theatre directors, composers, costume designers, artists and performers to literature. Diaghilev caught the attention of such writers as Marcel Proust, James Joyce, Jean Cocteau, the Sitwells, Leonard Woolf, indeed, the Bloomsbury group in general, T. S. Eliot, Rupert Brooke, E. M. Forster, and, of course, D. H. Lawrence, too. While this has all been noted in biographies and memoirs, few scholars have considered the possible reasons behind the company's creation. Why would a man who had aligned himself with sumptuous and highly successful art exhibitions and demonstrated such strong passion for opera turn to ballet? Any attempt to answer such a question requires an exploration of the events in Diaghilev's life from his St. Petersburg years to the Paris years and early seasons of the Ballets Russes (1895-1913). Two names recur throughout these years: Oscar Wilde and Aubrey Beardsley-in person, in writing, and in spirit. A review of Diaghilev's career between 1895 and 1913 together with a textual study of some early ballets suggest that Wilde and Beardsley may have had a stronger influence on Diaghilev and the creation of the Ballets Russes than has previously been noticed.